Comparison of the accuracy of plastic and metal stock trays for implant impressions - Del’Acqua, Marcelo Antonialli (2012)
Purpose: This in vitro study evaluated the dimensional accuracy of two impression techniques (tapered and splinted) with two stock trays (plastic and metal) for implant-supported prostheses. Materials and Methods: A master cast with four parallel abutment analogs and a passive framework were fabricated. Polyvinyl siloxane impression material was used for all impressions with two metal stock trays and two plastic stock trays (closed and open trays). Four groups (tapered plastic, splinted plastic, tapered metal, and splinted metal) and a control group (master cast) were tested (n = 5 for each group). After the framework was seated on each of the casts, one abutment screw was tightened, and the marginal gap between the abutment and framework on the other side was measured with a stereomicroscope. The measurements were analyzed with the Kruskal-Wallis one-way analysis of variance on ranks test followed by the Dunn method. Results: The mean values (± standard deviations) for the abutment/framework interface gaps were: master cast, 32 ± 2 µm; tapered metal, 44 ± 10 µm; splinted metal, 69 ± 28 µm; tapered plastic, 164 ± 58 µm; splinted plastic, 128 ± 47 µm. No significant difference was detected between the master cast, tapered metal, and splinted metal groups or between the tapered and splinted plastic groups. Conclusions: In this study, the rigidity of the metal stock tray ensured better results than the plastic stock tray for implant impressions with a high-viscosity impression material (putty). Statistically similar results were obtained using tapered impression copings and splinted squared impression copings. The tapered impression copings technique and splinted squared impression copings technique with a metal stock tray produced precise casts with no statistically significant difference in interface gaps compared to the master cast. © 2012 by Quintessence Publishing Co Inc.